Management of lower extremity soft-tissue sarcoma in a sub-saharan african teaching hospital: case reports (2019)
Background: Soft-tissue sarcomas are relatively rare tumors and can occur in many parts of the body. When they affect the body extremities, their management can be challenging, often leading to limb amputation. Recent advances in surgery, adjuvant therapy, and better collaboration among different surgical specialists, medical and radiation oncologists, coupled with management in specialized centers have led to an upsurge in limb preservation. However, this is not obtainable in many centers in the developing countries. We report cases of soft-tissue sarcoma of the lower limb in two patients managed in a tertiary center in sub-Saharan Africa and the challenges encountered in their management. Case Reports: Two patients presented to our hospital with progressive painless masses on the lower third of their legs. Evaluation suggested that the masses were malignant. They both had wide local excision. The first patient had reconstruction with island sural artery fasciocutaneous flap, whereas the second had reconstruction with freestyle propeller flap. The postoperative periods were uneventful, and timely adjuvant therapy was commenced. Limb function was preserved in the two patients. Conclusion: Treatment of soft-tissue sarcomas of the limbs could be tasking, but multispecialty surgical intervention and adequate adjuvant therapy could give favorable result and a functional limb postoperatively.